The Application of Experimental Methods to Improve Science Learning Outcomes for Fourth Grade Students at Elementary School - Aman Sugianto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this research was to improve the learning outcomes of fourth grade students at SD Negeri Pabuaran 02 in science subjects through the application of experimental methods. The research that was conducted was Classroom Action Research (CAR) which was carried out in two cycles of action, each cycle consisting of two meetings. The stages for each cycle are planning, implementation, observation and reflection. Data was collected using observation techniques, documentation studies and tests. The results of the first cycle of research showed that students who completed the post-test were 63.6%. In the implementation of the second cycle of students who completed after carrying out the post test was 95.5%. These results indicate that the application of the experimental method can improve student learning outcomes in science subjects Class IV at SD Negeri Pabuaran 02, especially on the material properties of light.